Demonstrasi Mahasiswa PMII terkait Kebijakan Pemerintah di Kabupaten Lumajang: Partisipasi Mahasiswa dalam Menyuarakan dan Menyalurkan Aspirasi Masyarakat - Ahmad Zidan; Thifli Ahmad; Yusril Huda (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2023)
Demo stands for demonstration which refers to the act or process of showing, demonstrating, or explaining something to others. It can be a live action or a presentation to illustrate how something works, how a product or service is used, or how a concept or idea is implemented. A demonstration is an act or attempt to show or demonstrate something, whether in the context of expressing an opinion, spraying a message, or conveying information to a public audience. Demonstrations are often conducted by groups or individuals to create awareness, influence change, or communicate a particular message. This research has several main objectives, namely to understand the initial chronology that led PMII to conduct a demonstration at the Lumajang district government office, the district government's reaction or response to the protest against the Lumajang regent and the chairman of the DPRD, the content of the messages conveyed by PMII during the demonstration, and the efforts or solutions proposed to overcome the problem. The research methods used include news analysis and field research.